Could God Incarnate as an Animal? : Putting Bonaventure & Aquinas into Dialogue with Wallace’s Christian Animism - Dumsday, Travis (TheoLogica, 2026)
In Mark Wallace’s When God Was a Bird: Christianity, Animism, and the Re-Enchantment of the World (Fordham University Press, 2019), two interrelated claims are pursued: (1) that Christianity and animism are complementary; and, (2) that the Holy Spirit literally became incarnate as a bird at Christ’s baptism. In this paper I mostly focus on the second claim, bringing his view into dialogue with those of two mediaeval Scholastics who remain highly influential in Catholic thought: St. Bonaventure and St. Thomas Aquinas. I examine what they have to say on two questions relevant to assessing Wallace’s striking claim regarding the Spirit’s avian incarnation: first, whether the Holy Spirit could become incarnate at all; and second, the question of whether any divine Person could become incarnate in a non-rational nature.